Effective dominance and redundant killing of single‐ and dual‐gene resistant populations of Helicoverpa zea on pyramided Bt corn and cotton. Issue 10 (12th July 2022) - Santiago‐González, José C; Kerns, David L; Head, Graham P; Yang, Fei
Abstract: BACKGROUND: Pyramided Bacillus thuringiensis (Bt) crops producing multiple Bt proteins with different modes of action are widely planted in the United States. Helicoverpa zea is a major target pest of pyramided Bt crops and has evolved practical resistance to both Cry1 and Cry2 proteins in some regions of U.S. However, little information is available regarding redundant killing and the dominance of resistance for insects possessing multiple resistance on pyramided Bt crops. In this study, we evaluated redundant killing and the dominance of resistance for H. zea strains resistant to Cry1 or Cry1 + Cry2 on pyramided Bt corn and cotton. RESULTS: We found that the Cry1‐resistant H. zea was incompletely dominant on Cry1Ac + Cry1F cotton. Pyramided crops producing Cry2 and/or Vip3Aa proteins showed a complete redundant killing against the Cry1‐resistant H. zea . The Cry1 + Cry2‐resistant H. zea displayed incompletely recessive to completely dominant resistance on pyramided Bt crops containing Cry1 and/or Cry2 proteins. The redundant killing was complete for the Cry1 + Cry2‐resistant H. zea on pyramided Bt crops producing Vip3Aa protein. CONCLUSION: The dominant resistance of Cry1 and Cry2 in H. zea on pyramided Bt crops deviates from the assumption of functionally recessive resistance underlying the high‐dose refuge strategy. However, the assumptions of complete redundant killing are achieved for both Cry1‐ and Cry1 + Cry2‐resistant H. zea on pyramided Bt crops. These results suggest that the pyramided strategy could be valuable for increasing the durability of Bt technology for managing H. zea, a pest with inherently low susceptibility against Cry proteins. © 2022 Society of Chemical Industry. Abstract : The dominant resistance of Cry1 and Cry2 in H. zea deviates from the assumption of functionally recessive resistance underlying the high dose refuge strategy. The assumptions of complete redundant killing are achieved for both Cry1‐ and Cry1 + Cry2‐resistant H. zea on pyramided Bt crops.